THE PERFORMANCE OF REVERSE OSMOSIS MEMBRANE IN WATER TREATMENT - Budiyono Budiyono; Luqman Buchori (Diponegoro University, 2008)
Membrane technology has led to a new focus on water and wastewater treatment. This is due to severaldrawback of the conventional water treatment i.e release the toxic and carcinogenic materials. In thisresearch, the use Reverse Osmosis (RO) membrane for treating river and well water to obtain clean anddrinking water was studied. The variables studied were effect of pressure and operation time to themembrane flux. The pressure was varied from 1 to 7 bar and the operation time was varied from 15 to 60minutes. The content of Total Dissolved Solid (TDS) in the permeate product was analyzed. The resultsshown that the increase of pressure would increase the membrane flux and decrease TDS. The increaseof the operation time would decrease membrane flux and TDS. The reverse osmosis membrane wassuccessfully applied to treat the river and well water. The product fulfill national standard quality ofdrinking water by viewpoint of the TDS content